MINAT KUNJUNG PEMUSTAKA PADA PERPUSTAKAAN SEKRETARIAT DAERAH PROVINSI KALIMANTAN BARAT - Huda, Muhammad Hudri Alamal; Saman, Sisilya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis final project discusses the library facilities and the interest of visiting visitors in the Regional Secretariat Library of West Kalimantan Province. The formulation of the problem of this research is what are the factors that influence the lack of user interest in the Regional Secretariat Library of West Kalimantan Province? and the efforts of the manager of the West Kalimantan Regional Secretariat in increasing the interest of visitors in the Regional Secretariat Library of West Kalimantan Province? The purpose of this study is to find out what factors influence the lack of interest of visitors in the Regional Secretariat Library of West Kalimantan Province, for efforts to manage the secretary of West Kalimantan Regional Library in increasing the interest of visitors in the Regional Secretariat Library of West Kalimantan Province. This type of research is an associative research with a quantitative approach. The population in this study was the average of visitors who visited for the last 3 months, namely 58 visitors, while the study sample used the Slovin formula with accidental sampling technique obtained by 58 respondents. Data were collected using a questionnaire that was distributed directly to respondents.Keywords : Visit Interests, Visitors, Library of Regional Secretariat